Assessing the clinical severity of type 1 von Willebrand disease patients with a microchip flow‐chamber system. (15th March 2016) - Nogami, K.; Ogiwara, K.; Yada, K.; Shida, Y.; Takeyama, M.; Yaoi, H.; Minami, H.; Furukawa, S.; Hosokawa, K.; Shima, M.
Abstract : Essentials von Willebrand factor levels don't always reflect the severity of von Willebrand disease (VWD). Relationship between new flow system (T‐TAS ® ) and bleeding score (BS) in type 1 VWD was studied. Patients with PL‐T10 > 10 min had higher BS and particularly, PL‐T10 > 8 min correlated best. T‐TAS could be a useful tool for discriminating and predicting the BS in VWD type 1 patients. Summary: Background: The clinical phenotype of von Willebrand disease (VWD) is heterogeneous, and von Willebrand factor ristocetin cofactor activity (VWF:RCo) does not always reflect clinical severity, especially in VWD type 1. We have reported the potential of a microchip flow‐chamber system (Total‐Thrombus Formation Analysis System [T‐TAS ® ]) for assessing physiologic hemostasis in VWD. Aim: To evaluate the relationship between T‐TAS, bleeding score (BS) and laboratory test results in type 1 VWD patients. Methods: Microchips coated with collagen (platelet chip [PL‐chip]) or collagen/thromboplastin (AR‐chip) were used to assess platelet thrombus formation (PTF) at high shear rates or fibrin‐rich PTF at low shear rates, respectively, in whole blood from 50 patients. The times needed for the flow pressure to increase by 10 kPa and 30 kPa (T10 and T30 ) from baseline were calculated from flow pressure curves. BS was determined by the use of a standardized questionnaire. Results: PL‐T10 values correlated with BS ( R 2 0.45) better than VWF:RCo ( R 2 0.36), irrespective of the flow rate, whereas AR‐T10 showed only a weak correlation with BS ( R 2 0.18). Patients with PL‐T10 > 10 min or AR‐T10 > 30 min had lower VWF levels and higher BS than those with PL‐T10 ≤ 10 min or AR‐T10 ≤ 30 min, and the greatest differences were observed with PL‐T10 . Clinical severity appeared to correlate best with PL‐T10 > 8 min. BS was significantly higher in patients with VWF:RCo of < 10 IU dL −1 than in those with VWF:RCo of 10 IU dL −1 to < 25 IU dL −1 and 25–40 IU dL −1 . In patients with VWF:RCo of < 10 IU dL −1, BS was significantly higher in those with PL‐T10 > 8 min than in those with PL‐T10 ≤ 8 min. Conclusion: T‐TAS could be a useful technique for discriminating and predicting BS in VWD type 1 patients.